The Effect of Honey on Plasma Malondialdehyde (MDA) Level onAlloxan-Induced hyperglycemic Rats An Experimental studies in rats Galur Wistar White Males - Fajrilah, Bela Risqiyani; Indrayani, Ulfah Dian; Djam’an, Qathrunnada (Sains Medika : Jurnal Kedokteran dan Kesehatan, 2013)
Malondialdehyde (MDA) is the end product of lipid peroxidation and a marker of free radicals. Honey is a safe sweetener proven to lower blood glucose level and contains flavonoids, vitamin A, C, E as a source of antioxidant that can capture free radicals. This study aims to determine the effect of honey on plasma MDA level ionalloxan-induced hyperglycemicrats. This was an experimental study with post-test only control group design conducted for 25 days using 18 white male Wistar rats divided into 3 groups randomly. A negative control group, group B were given honey orally at the dose of 0.54 ml/mice/day, and group C were given honey orally at the of dose 0.9 ml/head/day. Each group consisted of 6 rats. Blood plasma MDA was evaluated by Thiobarbituric Acid Reactive Substance (TBARS) test assay. One way ANOVA analysis test followed post hoc were applied for data analysis. The results showed that mean levels of MDA in group A, B, and C were 6.02 mmol/l ± 0.36, 4.37 mmol/± 0.30, and 1.12 mmol/l ± 0.11 respectively. Bivariate analysis One way ANOVA test showed a significant difference (p<0,05). Post hoc tests showed a significant differences between the study groups (p<0,05). It can be concluded that honey had an effect on the levels of malondialdehyde (MDA) in the blood plasma of alloxan-induced hyperglycemic rats.